An efficient synthesis of novel spiro[indole-3, 8′-pyrano[2, 3-d][1, 3, 4]thiadiazolo[3, 2-a]pyrimidine derivatives via organobase-catalyzed three-component reaction of malononitrile, isatin and heterocyclic-1, 3-diones. (2nd November 2021) - Hosseini, Saedehsadat; Esmaeili, Abbas Ali; Khojastehnezhad, Amir; Notash, Behrouz
Abstract : In this research, firstly, some derivatives of sulfur containing [1, 3, 4]thiadiazolo[3, 2- a ]pyrimidin-5-one have been synthesized and then they were used for the synthesis of novel derivatives of 6′-amino-2, 9′-dioxo-2′-phenyl-9′ H -spiro[indoline-3, 8′-pyrano[2, 3- d ][1, 3, 4]thiadiazolo[3, 2- a ]pyrimidine]-7′-carbonitriles via a one-pot three-component condensation reaction of 7-hydroxy-2-phenyl-5 H -[1, 3, 4]thiadiazolo[3, 2- a ]pyrimidin-5-one derivatives, malononitrile and isatin compounds in the presence of DABCO as a organocatalyst and under solvent-free conditions. In this report, a new family of spiro-pyrano-thiadiazolo-pyrimidine derivatives have been synthesized in short reaction times (10–60 min) and good to excellent yields (80–96%). The structures of all synthesized products have been confirmed by IR, 1 H NMR, 13 C NMR and mass spectrometry, and the structure of one selected product was characterized by single-crystal X-ray diffraction studies as well. GRAPHICAL ABSTRACT: UF0001